Revitalisasi Perpustakaan Sebagai Sarana Literasi Anak-Anak di Desa Campuranom - Rio Galang Muslim; Ahmad Guspul; Riva Amelia Ramadhani; Ida Royani; Denanda Yustika Sari; Amalia Larasati; Ade Abdul Rozak; Dian Mukti Handini; Eka Septi Wijayanti; Erlinda Erlinda; Chana Nafisah; Sofwan Chanan; Mohamad Nikmatulloh; Zaenal Muttaqin (Universitas Palangka Raya, 2025)
Campuranom Village is located in Bansari District, Temanggung Regency, where the majority of the population are farmers. As a result, literacy and formal education for children are often overlooked. This article aims to explore the potential of library revitalization as a literacy facility for children in Campuranom Village. By combining theoretical and empirical analysis, this study employs the Participatory Action Research (PAR) method. The results indicate that the revitalization of the Campuranom Village Library was carried out through physical improvements, literacy program socialization, and evaluation. Physical improvements included cleaning the library, organizing books through labeling and categorization, and creating a reading corner to attract children's interest. Socialization was conducted to reintroduce the library’s function to the community, particularly schoolchildren. Evaluation was conducted at each stage to ensure the program’s effectiveness. As a result, children's visits to the library increased to 5-10 visitors per day, demonstrating a rise in reading interest. However, some challenges remain, such as poor ventilation making the library uncomfortably hot and its location on the second floor, which makes access difficult. Overall, the revitalization successfully enhanced the library’s appeal, though further improvements are needed in comfort and accessibility.